Men at Work
XII, 165 p.
Keywords: Men at Work explores the cultural portrayal of four essential wartime occupations: agriculture, industry, firefighting and the mercantile marine. In analysing a broad spectrum of wartime media (most notably film, radio and visual culture) it establishes a clear hierarchy of masculine roles in British culture during the Second World War.